Perbaikan Mutu Minyak Kelapa Sawit Curah dengan Metode Adsorpsi dalam Tangki Berpengaduk - Dena Sukantala Dewi; Ainun Farah Baiqfirlana; Bambang Sugiarto; Zubaidi Achmad (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2017)
This research objective is to improve the quality of Crude Palm Oil (CPO). In general, CPO contain free fatty acid known as FFA. CPO purification is necessary to eliminate FFA. In this research, CPO purification conducted by using adsorption method with various adsorbent. The adsorbent has to be activated with NaOH 0,087 N before being used. The variable used are variation of adsorbent (zeolite, bioceramics, and carbon active), adsorbent size (mesh of 20,30, 40,80, 100), and mixing time (10, 20, 30, 40, and 50 minutes). CPO quality can be analyzed by acidic-alkaline method to measure the number of acid, proxyde, saponification, iodine, and water value. The result showed that the optimum condition occurred when using zeolite of 100 mesh and 50 minutes mixing time. Before adsorption, the measurement for number of acid, peroxide, saponification, iodine and water value are respectively 1,9889; 16; 150,0675; 19,6695; and 6,572%. While the measurement result after adsorption are 0,1989 for acid number; 2 for peroxide number; 200,5575 for saponification number; 45,684 for iodine number; and 0,242% for water value. Compare to SNI 01-3741-1995 Standar Mutu Minyak Goreng, the result showed that CPO quality is improved and in line with the SNI requirement.